Synthesis of novel quinazolinone and fused quinazolinones - Mahmoud, Mahmoud Refaee; El-Shahawi, Manal Mohamed; Abu El-Azm, Fatma Saber Mohamed (European Journal of Chemistry, 2011)
A number of novel quinazolinone derivatives have been synthesized using the readily obtainable 2-[(1Z,3E)-1-benzamido-4-phenyl-1,3-butadien-1-yl]-3,1-benzoxazin-4(H)one (1) via the reaction with different nitrogen nucleophiles such as azines, Schiff’s base, primary aromatic amines, diamines, hydrazine hydrate and hydroxylamine.